Proton in vivo spectroscopy of patients with hyperphenylalaninaemia - Hájek, M; Hejcmanová, L; Prádný, J (Neuropediatrics, 1993)
Changes in MR images and 1H spectra of 20 patients with hyperphenylalaninaemia were compared with data of controls. Major changes in T2 MR images were found in the periventricular area (20/19). Some patients showed lesions in MR images of basal ganglia (20/7) and in the cerebellum (20/4). The results of proton MR spectroscopy show no significant difference for NAA/Cr ratios but significant ones between the ratios of NAA/Cho (p = 0.97) and Cho/Cr (p = 0.98) of controls and patients with hyperphenylalaninaemia.
Keywords: Brain Diseases; kreatin; demyelinizační nemoci; Male; Female; dítě; nemoci mozku; magnetická rezonanční tomografie; Phenylketonurias; Phenylalanine; fenylalanin; fenylketonurie; Demyelinating Diseases; mozek; mužské pohlaví; Biopterins; ženské pohlaví; kyselina asparagová; Adult; Choline; Child; Brain; dospělí; cholin; Creatine; Magnetic Resonance Imaging; lidé; Aspartic Acid; biopteriny; Humans; mozek - chemie; Brain Chemistry